2011
DOI: 10.3109/15376516.2010.543943
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of lead acetate on rat bone marrow-derived mesenchymal stem cells toxicity: Role of apoptosis

Abstract: Lead exposure continues to be a significant public health problem. Osteoporosis, inhibition of fracture healing, and cartilage functional impairment have been reported from lead exposure. Mesenchymal stem cells (MSCs) are a bone marrow population of cells with the ability to differentiate into various cell types, particularly osteocytes and chondrocytes. Despite intensive investigation on the effect of lead poisoning on various cell types, there is very little if any report on the effect of lead on MSCs. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
3
14
0
1
Order By: Relevance
“…MSCs have been used as the model system for studies on effects of many chemicals including nerutoxicants on cell proliferation, survival and differentiation10,11,12 ) . Recently, it was reported that some toxicants such as arsenic and lead can induce apoptosis of MSCs13, 14 ) . Moreover, these studies have been widely concerned.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have been used as the model system for studies on effects of many chemicals including nerutoxicants on cell proliferation, survival and differentiation10,11,12 ) . Recently, it was reported that some toxicants such as arsenic and lead can induce apoptosis of MSCs13, 14 ) . Moreover, these studies have been widely concerned.…”
Section: Introductionmentioning
confidence: 99%
“…During apoptosis progress, proapoptotic proteins such as Bax and Bak are localized in the mitochondrial membrane where they increase membrane permeability. In the cytoplasm, the released cytochrome c conjugates with Apaf-1 and procaspase-9 to form the apoptosome complex that activates capase-9 and further activates caspase-3 to induce apoptosis [Sharifi and Mousavi, 2008;Sharifi et al, 2010Sharifi et al, , 2011.…”
Section: Ginger ( Z Officinalementioning
confidence: 99%
“…Direkt olarak kemikte birikim, kemik hücrelerinde toksik etkiye neden olabilir. Çeşitli klinik ve deneysel çalışmalarda kurşun maruziyetinin kemiğin mineral yoğunluğunu ve gücünü azalttığı, kondrosit ve osteoblast fonksiyonlarını inhibe ettiği ve kemik yapımında azalmaya neden olduğu gösterilmiştir (7)(8)(9)(10). İndirekt etkileri ise kemik mineral metabolizmasında görev alan hormonların sentezinden sorumlu olan endokrin organlar üzerine etki ederek kemik metabolizmasında değişikliğe neden olması ve gastrointestinal sistemden kalsiyum emiliminde azalmaya neden olarak D vitaminin aktifleşmesini önlemesiyle gerçekleşir (11)(12)(13).…”
Section: Kurşununclassified